2022
DOI: 10.1002/jdd.13010
|View full text |Cite
|
Sign up to set email alerts
|

Adopting artificial intelligence in dental education: A model for academic leadership and innovation

Abstract: Introduction:The continual evolution of dental education, dental practice and the delivery of optimal oral health care is rooted in the practice of leadership. This paper explores opportunities and challenges facing dental education with a specific focus on incorporating the use of artificial intelligence (AI). Methods: Using the model in Bolman and Deal's Reframing Organizations, the Four Frames model serves as a road map for building infrastructure within dental schools for the adoption of AI. Conclusion: AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Most communication channels will eventually be transformed by AI, necessitating the need for dental schools to educate current students about these significant advances in technology [ 11 ]. In addition to opening opportunities to train dental professionals to employ AI approaches in clinical practice, its adoption holds huge potential for improving healthcare and educational opportunities [ 6 , 12 ]. The dental community and regulatory authorities must implement the suggested criteria to properly digitalize dentistry education with AI technology.…”
Section: Discussionmentioning
confidence: 99%
“…Most communication channels will eventually be transformed by AI, necessitating the need for dental schools to educate current students about these significant advances in technology [ 11 ]. In addition to opening opportunities to train dental professionals to employ AI approaches in clinical practice, its adoption holds huge potential for improving healthcare and educational opportunities [ 6 , 12 ]. The dental community and regulatory authorities must implement the suggested criteria to properly digitalize dentistry education with AI technology.…”
Section: Discussionmentioning
confidence: 99%
“…Adoption of AI might facilitate existing operations and future innovation, while improving educational opportunities and healthcare services. 19 Future dental professionals will be more prepared to embrace the possibilities of AI-driven advancements if they receive a sound foundation in AI knowledge early in their training, thus raising the standards for dental practice.…”
Section: Discussionmentioning
confidence: 99%
“…Dental professionals must continually refresh their knowledge and abilities to remain at the cutting edge of dental breakthroughs. 19 Dentistry practitioners may become familiar with the most recent AI technology and best practices through continuing education (CE) courses designed for AI applications. These courses will make practitioners better equipped to integrate AI into their everyday practices, thus ensuring the best possible patient results and improving dental care.…”
Section: Discussionmentioning
confidence: 99%
“…Within the higher education landscape, it has been suggested that dental curricula at universities need to be updated due to the AI paradigm shift [ 9 , 12 , 13 ]. This involves defining a fundamental dental curriculum for both undergraduate and postgraduate levels and establishing learning outcomes related to dental AI [ 8 ].…”
Section: Introductionmentioning
confidence: 99%